Architecture and patterns for IT service management, resource planning, and governance : making shoes for the cobbler's children - Betz, Charles T. (Morgan Kaufmann, 2011)
Information technology supports efficient operations, enterprise integration, and seamless value delivery, yet itself is too often inefficient, un-integrated, and of unclear value. This completely rewritten version of the bestselling Architecture and Patterns for IT Service Management, Resource Planning and Governance retains the original (and still unique) approach: apply the discipline of enterprise architecture to the business of large scale IT management itself. Author Charles Betz applies his deep practitioner experience to a critical reading of ITIL 2011, COBIT version 4, the CMMI suite, the IT portfolio management literature, and the Agile/Lean IT convergence, and derives a value stream analysis, IT semantic model, and enabling systems architecture (covering current topics such as CMDB/CMS, Service Catalog, and IT Portfolio Management). The edition retains the fundamental discipline of traceable process, data, and system analysis that has made the first edition a favored desk reference for IT process analysts around the world. This best seller is a must read for anyone charged with enterprise architecture, IT planning, or IT governance and management. Lean-oriented process analysis of IT management, carefully distinguished from an IT functional model Field-tested conceptual information model with definitions and usage scenarios, mapped to both the process and system architectures Integrated architecture for IT management systems Synthesizes Enterprise Architecture, IT Service Management, and IT Portfolio Management in a practical way.